Effects of psycho-educational group intervention using cognitive restructuring on anxiety and academic achievement among high school students in Iran - Motevalli, Saeid (2013)
Test or exam anxiety is well-known and widespread educational problem which experienced by the majority of students and impair their academic achievement. The main purpose of this study was compared the effects of cognitive restructuring and study skill training on anxiety (state and trait anxiety component) and academic achievement among Iranian high school students. In the current study, 94 high school students were randomly assigned to receive either a cognitive restructuring or study skill training through eight sessions of psycho educational group therapy. The State-Trait Anxiety Inventory was used as the main research questionnaire to assess the students’ anxiety (state and trait anxiety) and students’ school result letter as an indicator of academic achievement. The raw data was analyzed using exploratory data analysis, descriptive data analysis, and inferential data analysis using two way repeated measure ANOVA, and One-way ANOVA. The results of repeated-measures ANOVA revealed that there were significant differences across the pre, post, and follow-up tests among the students in cognitive restructuring, study skills training and control groups on state and trait anxiety. The Results indicated that students’ state anxiety on pre, post, and follow-up tests among study groups are different, F (1.456, 133.327) = 104.57, p <.001, η2 = .535, f= 1.1. Similarly, the results indicated that students’ trait anxiety on pre, post, and follow-up tests among study groups are different, F (1.308, 973.714) = 164.211, p <.001, η2 = .643, f= .96. In addition, post-hoc pairwise comparison revealed that the mean difference of state anxiety between on post-test and follow-up was significant among control group and study skills training group and also between cognitive restructuring and study skills training. Moreover, post-hoc pairwise comparison revealed that the mean difference of trait anxiety between on post-test and follow-up was significant among control group and study skills training group and also between control group and cognitive restructuring. Finally, the ANOVA test revealed that there was a statistically significant difference in the mean of grade point average score among cognitive restructuring, study skills training and control group F (2, 91) =6.089, p =.003, η2 = 0.118. Hence, the study can conclude that study skills training intervention promote the decreasing levels of anxiety on both components (state and trait anxiety) and also increasing on students’ academic achievement. Meanwhile, cognitive restructuring could decrease only trait anxiety that related directly to the cognitive component of anxiety and no effects on students’ academic achievement and state anxiety.